Seasonal Variations and Hospitalization Due to Diabetic Foot Complications - ShaziaJehan MuhammadAteeq RiffatMehmood (Journal of Rawalpindi Medical College, 2013)
Background: To study the seasonal variations in presentation of diabetic foot complications Methods: In this descriptive study 231 patients, presenting with Diabetic foot complications, were included. Clinical presentation in different seasons and surgical management outcome were recorded . Results: Majority (60.17%) were female. 197 (85.02%) patients were known diabetics whereas 34 (14.71%) DM was diagnosed incidentally. Concomitant chronic arterial insufficiency was found in 13 patients. Seventy six patients (32.90%) out of total 231 were subjected to major lower extremity amputation. Out of these major amputations (22.07%) were performed in winter season. Majority (64.93%) presented in winter season and 35.04% presented in summer season Conclusion: There is seasonal variation in diabetic foot ulceration.Intensive patient education and clustering of medical services in winter might reduce the incidence of diabetic foot ulceration, hence amputations.